Modern mysteries explained and exposed - Mahan, Asa (J.P. Jewett, 1855)
I. Clairvoyant revelation of A.J. Davis.--II. Phenomena of spiritualism explained and exposed.--III. Evidence that the Bible is given by inspiration of the Spirit of God, as compared with the evidence that these manifestations are from the spirits of men.--IV. Clairvoyant revelations of Emanuel Swedenborg.